2006
DOI: 10.1016/j.margeo.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Depositional patterns at Drift 7, Antarctic Peninsula: Along-slope versus down-slope sediment transport as indicators for oceanic currents and climatic conditions

Abstract: Understanding the processes and phases of deep-sea sediment drift formation is essential for a reconstruction of their evolution. This leads to a better understanding of the properties of oceanographic currents active during drift formation and in turn to information on the climatic conditions. A system of sediment drifts at the Antarctic Peninsula Pacific rise has been chosen to learn more about the Neogene evolution of both current systems and palaeo-climate in that area. Drift 7 was extensively surveyed (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…Maldonado et al, 2005;Uenzelmann-Neben, 2006). Although typical contourite drift structures are not clearly observed in the WS-SS transect seismic data, the seismic profiles are too sparse to exclude their existence in the pre-glacial central Weddell deep-sea units.…”
Section: Pre-glacial (Pg) Regimementioning
confidence: 90%
See 1 more Smart Citation
“…Maldonado et al, 2005;Uenzelmann-Neben, 2006). Although typical contourite drift structures are not clearly observed in the WS-SS transect seismic data, the seismic profiles are too sparse to exclude their existence in the pre-glacial central Weddell deep-sea units.…”
Section: Pre-glacial (Pg) Regimementioning
confidence: 90%
“…10) across the Weddell Sea, allow the interpretation that the southern part of the APIS probably already grounded in the early Miocene or even Oligocene, and the WAIS in the Oligocene. Sampling, drilling and multichannel seismic reflection data analyses of Drift 7 on the Pacific margin of the Peninsula, suggest down-slope transport as a result of the growth of the Antarctic Peninsula ice sheet in the Early Miocene (~15 Ma and 9.5 Ma; Uenzelmann-Neben, 2006). This early Miocene/ Oligocene APIS and Oligocene WAIS expansion is not adequately reproduced by palaeoclimate models that suggested a late Mioceneearly Pliocene APIS grounding (7.94-5.12 Ma, Bart et al, 2005;Pollard and DeConto, 2009; Table 1), but consistent with the SHALDRIL findings .…”
Section: Transitional (T) Regimementioning
confidence: 99%
“…There is widespread evidence for bottom current activity since~9.6 Ma in this area and in the Bellingshausen Sea further to the west (e.g. Nitsche et al, 2000;Rebesco et al, 2002;HernandezMolina et al, 2004;Hillenbrand and Ehrmann, 2005;Scheuer et al, 2006b;Uenzelmann-Neben, 2006). Uenzelmann-Neben and Gohl (2012) inferred bottom current activity as early as the Paleogene and the onset of major glaciations in West Antarctica at 14.1 Ma from seismic reflection profiles on the continental rise in the Amundsen Sea, but chronological control was poor.…”
Section: Palaeoenvironmental Settingmentioning
confidence: 96%
“…On the basis of seismic reflection profiles from the western Antarctic Peninsula margin that were correlated with drill cores, Rebesco et al (2002) and Uenzelmann-Neben (2006) identified a close interaction of contouritic and turbiditic sediment transport with indications for a major advance of the local ice sheet shortly after 15 Ma. There is widespread evidence for bottom current activity since~9.6 Ma in this area and in the Bellingshausen Sea further to the west (e.g.…”
Section: Palaeoenvironmental Settingmentioning
confidence: 99%
“…5, 9C). These drift bodies developed during the transport of sediments by a combination of contour currents and/or turbidity flows (Michels et al, 2001;Uenzelmann-Neben, 2006), fed by an abundance of glacial sediments brought to the basin margin cycles of ice sheet advanced and retreat.…”
Section: Full-glacial Phasementioning
confidence: 99%